The CULTURA Project: CULTivating Understanding and Research through Adaptivity - LAWLESS, SEAMUS (My University, 2011)
CULTURA will deliver personalisation and community-aware adaptivity for Digital Humanities communities through an innovative environment which is tailored to the investigation, comprehension and enrichment of digital humanities collections. CULTURA seeks to stim- ulate and support the communities of interest which form around such collections.
PUBLISHED
Keywords: Computer Science and Engineering; Digital Humanities; CULTURA Project